2004
DOI: 10.1128/jvi.78.24.13987-14002.2004
|View full text |Cite
|
Sign up to set email alerts
|

Attenuating Mutations in Coxsackievirus B3 Map to a Conformational Epitope That Comprises the Puff Region of VP2 and the Knob of VP3

Abstract: Ten antibody escape mutants of coxsackievirus B3 (CVB3) were used to identify nucleotide substitutions that determine viral virulence for the heart and pancreas. The P1 region, encoding the structural genes of each mutant, was sequenced to identify mutations associated with the lack of neutralization. Eight mutants were found to have a lysine-to arginine mutation in the puff region of VP2, while two had a glutamate-to-glycine substitution in the knob of VP3. Two mutants, EM1 and EM10, representing each of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0
6

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 46 publications
1
40
0
6
Order By: Relevance
“…13 Remarkably, many aspects of viral myocarditis may be recapitulated in experimental autoimmune models as induced by cardiac myosin and an adjuvant. 14 Pathological outcome of CVB3-induced myocarditis is determined by a complex interplay between viral [15][16][17][18] and host factors. At least two host proteins, decay accelerating factor (DAF) 19 and coxsackievirus-adenovirus receptor (CAR), 20,21 function as receptors for virus attachment and entry through binding with virus capsid proteins.…”
Section: Introductionmentioning
confidence: 99%
“…13 Remarkably, many aspects of viral myocarditis may be recapitulated in experimental autoimmune models as induced by cardiac myosin and an adjuvant. 14 Pathological outcome of CVB3-induced myocarditis is determined by a complex interplay between viral [15][16][17][18] and host factors. At least two host proteins, decay accelerating factor (DAF) 19 and coxsackievirus-adenovirus receptor (CAR), 20,21 function as receptors for virus attachment and entry through binding with virus capsid proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Like the Puff region of VP2, the Knob region of VP3 is known to contain a major neutralization site for both poliovirus and rhinovirus [30,32]. Furthermore, mutations in the VP3 Knob region have been suggested to have a role in the CVB3-induced cardiovirulence [31]. Whether or not the nonsynonymous mutations detected in the capsid region of the three clinical isolates play a role in virulence and pathogenesis of enterovirus infection, needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The three clinical isolates in this study had amino acid substitutions in the Puff region of the VP2 protein. Amino acid substitutions in the Puff region of CVB3 VP2 protein were previously linked to cardiovirulence [31]. Like the Puff region of VP2, the Knob region of VP3 is known to contain a major neutralization site for both poliovirus and rhinovirus [30,32].…”
Section: Discussionmentioning
confidence: 99%
“…The construction of the infectious clones pCVB3(KR) and pCVB3(EG) was previously described (26). The plasmid pCVB3(KR) has a single mutation of A to G at nucleotide 1421, resulting in a lysine (K)-to-arginine (R) substitution at amino acid 158 of the capsid protein VP2 (K2158R), while pCVB3(EG) contains a single mutation of A to G at nucleotide 1916, resulting in a glutamic acid (E)-to-glycine (G) substitution at amino acid 60 of VP3 (E3060G).…”
Section: Methodsmentioning
confidence: 99%
“…In 1996, a single amino acid substitution in the puff region of VP2 (asparagine to aspartate at amino acid 165) was found to reduce the myocardicity of a CVB3 mutant, H310A1 (14). Recently, we identified two mutations in the capsid proteins that affected cardiovirulence in studies of a panel of "escape" mutants (EMs 1 to 10) derived by treating a parental myocarditic strain, CVB3(RK), with a highly neutralizing monoclonal antibody (26). Two mutations were identified that were associated with both a lack of neutralization by the monoclonal antibody and reduced cardiovirulence.…”
mentioning
confidence: 99%